Determining Pharmaceutical Product Costs: Scientific and Practical Issues in Uzbekistan - Khudaynazarova Dilnoza Gafurovna (Academia Open, 2026)
This study addresses the scientific and practical challenges of determining finished product costs in pharmaceutical enterprises operating in the Republic of Uzbekistan, a critical issue in the context of economic reforms, stricter state regulation of drug pricing, and the ongoing transition to International Financial Reporting Standards that demand modern cost accounting systems. The research aims to identify deficiencies in current cost determination practices and propose improved methodologies tailored to the unique technological, regulatory, and organizational characteristics of pharmaceutical firms. Employing analytical, comparative, and monographic methods, the study examines actual accounting records and internal management reports from pharmaceutical enterprises, with particular attention to cost allocation across supply, production, laboratory testing, and packaging processes, and compares cost structures between imported and domestically manufactured products. Results reveal that material costs dominate the cost structure at approximately 50 percent, while wages and depreciation together account for nearly 30 percent; however, existing reporting practices fail to adequately disclose the distribution of indirect costs across production stages, limiting managerial control effectiveness. The novelty of this research lies in developing context-specific definitions for pharmaceutical business processes and proposing enhanced reporting formats that improve cost transparency and align with international standards. These findings have significant implications for strengthening management decision-making capabilities, improving financial reporting quality, and facilitating compliance with International Financial Reporting Standards in Uzbekistan's pharmaceutical sector.Keywords : Pharmaceutical Costing, Cost Allocation Methods, Financial Reporting Transparency, Indirect Cost Distribution, International Accounting Standards, Production Cost StructureHighlight : Material costs dominate pharmaceutical product costs, averaging 50 percent of total expenses. Current reporting inadequately discloses indirect cost allocation across production stages and functions. Study introduces simplified definitions and enhanced formats improving cost transparency and managerial control.